Inhibition of Mycobacterial Growth In Vitro following Primary but Not Secondary Vaccination with Mycobacterium bovis BCG - Fletcher, Helen A. (American Society for Microbiology, 2013)
Despite the widespread use of the Mycobacterium bovis BCG vaccine, there are more than 9 million new cases of tuberculosis (TB) every year, and there is an urgent need for better TB vaccines. TB vaccine candidates are selected for evaluation based in part on the detection of an antigen-specific gamma interferon (IFN-γ) response. The measurement of mycobacterial growth in blood specimens obtained from subjects immunized with investigational TB vaccines may be a better in vitro correlate of in vivo vaccine efficacy. We performed a clinical study with 30 United Kingdom adults who were followed for 6 months to evaluate the abilities of both a whole-blood- and a novel peripheral blood mononuclear cell (PBMC)-based mycobacterial growth inhibition assay to measure a response to primary vaccination and revaccination with BCG. Using cryopreserved PBMCs, we observed a significant improvement in mycobacterial growth inhibition following primary vaccination but no improvement in growth inhibition following revaccination with BCG (P < 0.05). Mycobacterial growth inhibition following primary BCG vaccination was not correlated with purified protein derivative (PPD) antigen-specific IFN-γ enzyme-linked immunospot (ELISPOT) responses. We demonstrate that a mycobacterial growth inhibition assay can detect improved capacity to control growth following primary immunization, but not revaccination, with BCG. This is the first study to demonstrate that an in vitro growth inhibition assay can identify a difference in vaccine responses by comparing both primary and secondary BCG vaccinations, suggesting that in vitro growth inhibition assays may serve as better surrogates of clinical efficacy than the assays currently used for the assessment of candidate TB vaccines.